Evaluating transport decarbonisation policies under carbon budget constraints: The role of carbon pricing and ICE bans - Daniel Cassidy; Kelly C. De Bruin (The Economic and Social Research Institute (ESRI), 2025)
This paper develops and applies I3E-Transport, a new passenger transport model for Ireland that integrates behavioural, technological, and macroeconomic drivers to assess the effectiveness of two decarbonisation policies-carbon taxation and internal combustion engine (ICE) phase-outs-on emissions from private cars and public transport by bus, rail, and light rail. The model is linked to the Ireland Environment-Energy-Economy (I3E) Computable General Equilibrium framework, allowing for a comprehensive evaluation of how policy measures affect transport demand, vehicle stock composition, energy consumption, and emissions within the constraints of Ireland's carbon budgets. Simulation results for 2024-2050 show that, under a business as usual baseline scenario, emissions are projected to increase steadily through 2040, driven by income and population growth. A modest decline follows between 2040 and 2050, reflecting gradual uptake of alternative vehicles and improvements in fuel efficiency. However, 2050 emissions are projected to still exceed current levels, indicating limited overall progress without further policy intervention. A carbon tax delivers only marginal abatement, while a comprehensive ICE vehicle ban from 2035-including hybrids-reduces CO₂ emissions by nearly six million tonnes relative to the baseline by 2050. Nevertheless, the sector remains off course for compliance with its 2030 abatement target and carbon budgets ceilings for 2031-2035 and 2036-2040, reaching them only in the late 2030s even under the most ambitious scenario. Earlier implementation and accelerated public transport electrification could advance compliance modestly but not fully bridge the gap. The findings highlight that timely and coordinated policy action-combining regulatory, fiscal, and behavioural instruments-is essential to align Ireland's transport sector with its long-term climate commitments.
Keywords: Q54; Q58; R41; R48; C63; 330; Transport decarbonisation; ICE bans; Carbon taxation; Passenger transport modelling; Vehicle stock; Electric vehicles; Carbon budgets; Ireland